2010
DOI: 10.1007/s00270-010-9849-3
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency Ablation of Intrahepatic Cholangiocarcinoma: Preliminary Experience

Abstract: The purpose of this study was to evaluate the safety and efficacy of percutaneous ultrasound (US)-guided radiofrequency ablation (RFA) in patients with intrahepatic cholangiocarcinoma (ICCA) in a small, nonrandomized series. From February 2004 to July 2008, six patients (four men and two women; mean age 69.8 years [range 48 to 83]) with ICCA underwent percutaneous US-guided RFA. Preintervetional transarterial embolization was performed in two cases to decrease heat dispersion during RFA in order to increase th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
68
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 20 publications
2
68
0
1
Order By: Relevance
“…Owing to restricted resources of liver donors and poor prognosis after liver transplantation, transplantation for ICC remains a controversial area. Furthermore, there are not standard chemotherapeutic protocols for ICC [24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Owing to restricted resources of liver donors and poor prognosis after liver transplantation, transplantation for ICC remains a controversial area. Furthermore, there are not standard chemotherapeutic protocols for ICC [24].…”
Section: Discussionmentioning
confidence: 99%
“…A 78-year-old man with a solitary ICC was successfully treated by RFA and remained free of disease after a follow-up of 24 months. Since then, thermal ablation has been increasingly applied in treating ICC, including both RFA and MWA [7,24,[28][29][30]. The complete ablation rates for ICC,5 cm were 88-97% [7,29].…”
Section: Discussionmentioning
confidence: 99%
“…However, Giorgio et al reported that it is difficult to achieve complete ablation during the 1st session when the tumor size exceeds 4 cm, while complete ablation was always achieved for smaller nodules equal to or less than 3.4 cm (16). In multivariate analyses in previous studies, tumor size was identified as the main factor predicting the initial effectiveness of RFA, as well as the survival outcomes after RFA (13,19).…”
Section: Indication and Technical Considerationmentioning
confidence: 99%
“…However, the local tumor progression rate after RFA was relatively high, ranging from 8% to 50% (12)(13)(14)(15)17,19,20), and the pooled rate in a meta-analysis was reported to be 21% (95% CI, 13-30%) (11). The rate of major complication observed after RFA was 8% in the evaluable population, as shown in Table 1.…”
Section: Effectiveness Of Rfamentioning
confidence: 99%
See 1 more Smart Citation